2021
DOI: 10.31217/p.35.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Deviations and errors review on measuring and calculating heavy fuel oil consumption and fuel stock onboard vessels equipped with volumetric fuel consumption flowmeters

Abstract: A common way of measuring heavy fuel oil consumption on board a vessel is to use volumetric fuel flow meters installed at fuel systems inlets for each of the major fuel consumers. At each stage of the fuel processing cycle, certain mass fuel losses or deviations and calculation errors occur that are not counted accurately into fuel consumption figures. The goal of this paper is to identify those fuel mass losses and measuring/calculating errors and perform their quantitative numerical analysis based on actual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…0.099 during anchorage, 0.063 during navigation). Separated sludge figures present significant difference from the findings in Dujmović et al [9], where during steaming was identified 0.15% and 0.26% of separated components from consumed quantity of fuel. However, the percentage of 0.8% to 1.2% are in line with guidelines from International Maritime Organization [24].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…0.099 during anchorage, 0.063 during navigation). Separated sludge figures present significant difference from the findings in Dujmović et al [9], where during steaming was identified 0.15% and 0.26% of separated components from consumed quantity of fuel. However, the percentage of 0.8% to 1.2% are in line with guidelines from International Maritime Organization [24].…”
Section: Discussioncontrasting
confidence: 88%
“…However, some topics and areas in this research are covered in previous papers. The accuracy of fuel consumption calculation and separated fuel sediments quantity as a function of consumed fuel is presented in Dujmović et al [9]. Simulation and application of marine fuel oil purifier and sludge generation based on fuel flow through purifier bowl on Alfa Laval S series purifier is described by Ying et al [10].…”
Section: Introductionmentioning
confidence: 99%